Erratum: FERNANDES, F.A., FORNEL, R. & FREITAS, T.R.O (2012) Ctenomys brasiliensis Blainville (Rodentia: Ctenomyidae): clarifying the geographic placement of the type species of the genus Ctenomys. Zootaxa, 3272, 57–68. - Fernandes, F. S.; Fornel, R.; Freitas, T. R. O. (Zootaxa, 2012)
(Erratum)